2019
DOI: 10.1002/micr.30488
|View full text |Cite
|
Sign up to set email alerts
|

Use of the subscapular system by maintaining unilateral decubitus placement without repositioning in microvascular free tissue transplantation

Abstract: Background In microvascular free‐tissue harvest and transfer, the need for repositioning from lateral decubitus position and the inability to use a two‐team approach are major drawbacks of the subscapular system. We present our experience with the subscapular system for upper and lower extremity reconstruction using a two‐team approach without need for repositioning. Methods We conducted a retrospective chart review for all patients undergoing free flap transplant based on the subscapular system to the upper o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Forte et al reported subscapular system flap for upper and lower extremity reconstruction maintaining lateral decubitus without repositioning (Forte et al, 2020). They modified the extremity position to allow access to the recipient site in decubitus position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forte et al reported subscapular system flap for upper and lower extremity reconstruction maintaining lateral decubitus without repositioning (Forte et al, 2020). They modified the extremity position to allow access to the recipient site in decubitus position.…”
Section: Discussionmentioning
confidence: 99%
“…Sacral and right ischial pressure sore wounds became aggravated (Figure 4b,c) During 1 year of follow-up, there were no ulcers or tumor recurrence (Figure 4d). Forte et al reported subscapular system flap for upper and lower extremity reconstruction maintaining lateral decubitus without repositioning (Forte et al, 2020). They modified the extremity position to allow access to the recipient site in decubitus position.…”
Section: Casementioning
confidence: 99%